The use of Student Team Achievement Division (STAD) in Improving Students’ IPS learning achievement of Class IX F SMP N 21 Pontianak - Jumadi, Jumadi (Tanjungpura University, 2019)
This classroom action research aimed at improving learning quality and student learning achievement that are still low especially in the IPS learning process in class IX F of SMP Negeri 21 Pontianak. To overcome these problems, the cooperative method of Student Teams Achievement Division (STAD) was used. After applying the Student Teams Achievement Division (STAD), the students’ IPS learning achievement in class IX F was increased. This study was conducted in two cycles of 38 students. The technique of collecting data was through observation conducted by teachers and collaborators, and data analysis was carried out in descriptive with percentage techniques. The level of student and teacher activity stated as a very good, good, or moderate category. while the success of using the Student Teams Achievement Division (STAD) method was stated successfully, less successfully, or unsuccessfully.Based on the results of the research that had been done, it can be concluded as follows: 1) Student activity in the teaching and learning process was good because it had reached the specified criteria in which 81% of students were actively involved, 2) Teacher activities in learning process was very good because it reached 84%, 3) While the students’ learning achievement percentage reached 82% beyond the criteria of 75%. Thus, the use of the cooperative method of Student Teams Achievement Division (STAD) succeeded in improving student learning achievement in IPS learning in class IX F of SMP Negeri 21 Pontianak